Effects of alternative soy sources on growth performance in early-weaned pigs - Cabrera, M.R.; Rantanen, M.M.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 144 pigs (initial body wt of 10.4 lb) was used in a 56-d growth assay to determine the effects of different soybean preparations on growth performance and cost of gain in nursery pigs. Experimental diets were fed in three phases from d 0 to 35 postweaning (Le., d 0 to 7, 7 to 21, and 21 to 35). Treatments were a soybean meal-based regimen; a dry-extruded whole soybeans (mill-run) regimen; and a specially processed soy products regimen (Le., soy isolate in Phase I, soy concentrate in Phase 11, and extruded soy flour in Phase Ill). All diets were formulated to 1. 55, 1. 25, and 1.15% lysine for Phases I, 11, and III, respectively. Fat additions to the soybean meal and specialty soy product treatments were 2, 2, and 3%, for Phases I, 11, and III, respectively. The diets with extruded soybeans had more total fat (2.5, 3.8, and 4.8% greater percentage ether extract in Phases I, 11, and III, respectively) than the soybean meal-based control. On d 35 postweaning, the pigs were switched to the same soybean meal-based grower diet (.9% lysine) for a period of 3 wk. During Phase I (d 0 to 7 postweaning), pigs fed soybean meal gained 25% less and were 22% less efficient than those fed extruded soybeans and the specially processed soy products. Average daily feed intake was not affected by dietary treatment; however, pigs fed the specially processed soy product had the greatest ADG of any treatment, and numerically, the best efficiencies of gain. No statistical differences were found for ADG, ADFI, or F/G among treatments from d 7 to 21, 21 to 35, or 35 to 56 of the experiment. Thus, overall (from d 0 to 56 postweaning), pigs fed the various soybean protein sources had similar growth performance. However, overall costs per pound of gain were $.33, $.34, and $.42 for pigs fed extruded soybeans, soybean meal, and the specialty soy products, respectively. In conclusion, although the specially processed soy products regimen (Le., soy isolate) supported the greatest growth performance immediately after weaning (d 0 to 7), the best cost of gain was achieved by feeding extruded soybeans. However, the additional fat provided by extruded soybeans did not influence pig performance in this experiment.
Keywords: Swine; Pigs; Soybeans; Extrusion; Growth; Cost of gain